2016
DOI: 10.1186/s12885-016-2394-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing diagnosis delay of advanced breast cancer in Moroccan women

Abstract: BackgroundDelay in the diagnosis of breast cancer in symptomatic women of 3 months or more is associated with advanced stage and low survival. We conducted this study to learn more about the extent and reasons behind diagnosis delay of advanced breast cancer in Moroccan women.MethodsA group of patients with advanced breast cancer were interviewed at the National Institute of Oncology in Rabat during the period from February to December 2014. Diagnosis delay was devised into patient delay and system delay. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 29 publications
(26 reference statements)
7
52
1
2
Order By: Relevance
“…The known relevance of breast cancer awareness in the patients’ medical‐seeking behavior is confirmed in our findings. The association identified between the patients’ initial interpretations of breast symptoms as “not cancer” and “not worrisome” and postponement of seeking care has been described in previous studies . The results of the PA reveal that these initial interpretations are associated with higher cancer awareness indicators like knowing someone who had cancer, knowledge of mammography, and knowledge of BC symptoms.…”
Section: Discussionsupporting
confidence: 64%
“…The known relevance of breast cancer awareness in the patients’ medical‐seeking behavior is confirmed in our findings. The association identified between the patients’ initial interpretations of breast symptoms as “not cancer” and “not worrisome” and postponement of seeking care has been described in previous studies . The results of the PA reveal that these initial interpretations are associated with higher cancer awareness indicators like knowing someone who had cancer, knowledge of mammography, and knowledge of BC symptoms.…”
Section: Discussionsupporting
confidence: 64%
“…Starting use of T&CM before seeking care at biomedical facilities potentially delays health seeking. Other studies have shown that patients with cancer who take recourse to T&CM often delay by several months to be diagnosed and are often in advanced stage disease at presentation (Broom et al, ; De Boer, Niyonzima, Orem, Bartlett, & Zafar, ; Kerdpon & Sriplung, ; Maghous et al, ). These findings have important implications for interventions to promote early detection of cancers by targeting the THPs who are visited earlier on in the disease trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…The observed time interval was shorter in countries such as Thailand (Poum et al, ), Estonia (Innos et al, ) and Jordan (Abu‐Helalah et al, ) than observed herein, with medians of 12, 16, and 30 days, respectively. In Morocco (Maghous et al, ), Niger (Pace et al, ), China (Yau et al, ) and Uganda (Odongo et al, ), the delay exceeds 90 days. The largest time intervals described in the literature were 5 months in Niger (median), 6 months in Morocco (median), 13 months in Uganda (median) and 13.1 weeks in China (mean).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review (Walter et al, ), demographic, psychological and social factors are mentioned as some of the reasons contributing to the delay in this step (Andersen & Cacioppo, ). Women's liability concerning delays in breast cancer evaluation must be questioned and broadly discussed, due to social, political and economic barriers (Lim, Potrata, & Simonella, ; Maghous et al, ; Pace et al, ; Unger‐Saldaña, ; Unger‐Saldaña & Infante‐Castañeda, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation